An investigation of utilising hashtags to enhance teaching and learning experiences among art students / Syaryfah Fazidawaty Wan Busrah - Wan Busrah, Syaryfah Fazidawaty (Faculty of Art and Design, 2021)
This paper aims to investigate the visibility of students' artwork by utilising hashtags as a management tool to enhance their teaching and learning experiences. This study uses primary data analysis from 269 arts students from various universities in Malaysia who were randomly chosen. The questionnaires were distributed at these universities/colleges and sent online for the respondents to participate in the questionnaire. The data was analysed based on descriptive analysis such as frequency counts, validity and means by using Statistical Package for Social Sciences (SPSS). Based on the preliminary study, students have indicated that they prefer the lecturers to incorporate social media in their teaching and learning as they found it more relaxing and entertaining. By encouraging students to include hashtags to label their artworks via social media, the visibility of their artwork will be enhanced thus improving the chance for them to be discovered by potential employers.This paper concludes that by using hashtags, there is a significantly high level of potential for teaching and learning to be a more fun and engaging learning experience where students connect, share their artworks, gather ideas and receive comments from a wider audience including their peers, artists or even experts in the field.